MODEL SISTEM PAKAR DALAM MENGIDENTIFIKASI PERMASALAHAN PADA JARINGAN IRIGASI PERTANIAN DI BENDUNG TALAWAAN - Richard A.V. Koloay; David Rumambi; Robert Molenaar (Universitas Sam Ratulangi, 2018)
ABSTRACT Â This study aims to obtain information about the problems that occur in irrigation networks at the right part of Talawaan dam and produce a computer application model as an expert system. It is hoped that this expert system application can be useful to provide information about the problems that occur in the irrigation network in Talawaan dam, especially on right Talawaan irrigation networks and can provide solution of the problem through an expert system application that can be accessed by each user. This research was conducted in the Technical Laboratory of Agricultural Faculty of Agriculture Technology Department of UNSRAT and in Talawaan dam, Talawaan Subdistrict, North Minahasa Regency, North Sulawesi Province, and divided into two stages: irrigation network data collection and expert system application development. Â Data collection on right Talawaan dam is done by calculating inflow water discharge and outflow water discharge and evaporation on primary, secondary and tertiary channel then documentation on problems that occur on irrigation channel. There is a water loss of 0.187 m3 / sec on the primary channel, 0.213 m3 / sec of water loss in secondary channels, and water loss of 0.074 m3 / sec on tertiary channels. Factors that cause water loss include the problem of damage to irrigation channels, garbage accumulation, illegal water taking, and silting of channels by mud. With this expert system, users can get information on problems that occur on irrigation channels and can consult to find solutions to the problem. Â Keywords: Irrigation Network and Expert System